Seminario de fortran 77 - Facultad de ingeniería (My University, 1983)
The following summarizes the statements available in the vax-11 fortran language, including the general form of each statement. The statements are listed alphabetically for case of reference. The manual section column indicates the section of this manual that describes each statement in detail.
Keywords: arithmetic; character; relational; logical; extendsize; type declaration